Persepsi Kualitas Pelayanan Persepsi Anti Korupsi dan Kepuasan Layanan Badan Narkotika Nasional Provinsi (BNNP) Maluku Utara - Ardiyanti A. Dero; Sarbanun Umasangadji; Jamiludin Hasan (Yos Soedarso Economic Journal (YEJ), 2024)
This research uses a survey method with a cross-sectional time dimension, an explanation that aims to collect data on objects by taking samples from a population using a questionnaire as the main data collection tool. In determining the target population, it is necessary to consider limitations and criteria for the purpose of the survey, such as service users who access services via WhatsApp, email. The service time period is from January to December 2023 for 10 (ten) service products, namely: Drug Examination Results Certificate (SKHPN), P4GN Counseling, Internships and research, Outpatient rehabilitation, Rehabilitation assistance, Investigation Services, Capacity Development Services, Life Skills Technical Guidance Services, TAT Services. Based on the analysis of the results of the Service Quality Perception Survey on services at North Maluku BNNP, this research data concluded that the Service Quality Perception Index at North Maluku BNNP was. From the results of data processing for 371 respondents, the interval value for the IPKP survey was 3.91, with a value conversion interval 97.7. Service quality A, service unit performance is very good. Meanwhile, the Anti-Corruption Perception Index results have an interval value of 3.93, the conversion interval value is 98.2. Quality of service A. The performance of the service unit is free from corruption. Meanwhile, for service satisfaction, the interval value was 1.73, the conversion interval value was 43.2. Quality of service D. North Maluku BNNP service performance is not satisfied.